Land management and biodiversity maintenance: a case study in grasslands in the Coastal Plain of Rio Grande do Sul - Bonilha, Camila Leal; Andrade, Bianca Ott; Vieira, Mariana de Souza; da Silva Filho, Pedro Joel; Rolim, Rosângela Gonçalves; Overbeck, Gerhard Ernst; Boldrini, Ilsi Iob (Iheringia, Série Botânica., 2017)
Coastal grasslands are one of the most threatened types of grasslands in the southern Brazil. To evaluate if areas with diff erent landuse history diff er in current grassland species composition and structure, four areas were selected according to current management: Entisols areas used for extensive livestock breeding (GR1 and GR2 sites); Alfi sols areas used for rice production with fallow periods (GRC), and for rotation with soybean (GSB). In each area, soil and grassland vegetation were characterized. We verifi ed that GR1, GSB, GRC and GR2 sites followed a decreasing order of species richness. Despite the higher richness found in GSB and GRC sites, few native perennial species with high coverage were recorded, due to dominating exotics and annuals. In contrast, grasslands used for pasture presented the typical vegetation features. For eff ective conservation eff orts, we highlight the importance to keep grasslands on both soil types.